Prediction of elite male trampolines' performance based on the selected psychological capabilities - Ercis, S. (Journal of Education and Training Studies, 2018)
Main purpose of this study was prediction of elite male trampolines' performance based on the selected physical and psychological capabilities in different age categories. To this aim, 45 male athletes, athletic experience and competitive experience, who participated in the national trampoline team's preparation camps for participation at the 2014 Asian Games in four age categories included Children (ages 11 and 12 yrs), Juniors (ages 13 and 14 yrs), Adolescents (ages 15 to 17 yrs), and Seniors (ages 18 yrs <), were selected using targeted sampling as subjects. Variables of study included 16 variables related to mental skills which were measured using standard procedures and instruments. Data were analyzed using Pearson correlation coefficient and multiple regression models at the 0.05 significance level. Results of study showed that, among all relationships between variables, self-confidence (r=0.359), concentration (r=0.316), concentration recovery (r=0.394), average of psycho-cognitive skills (r=0.304), and total average of mental skills (r=0.307) with performance are statistically significant. Results of regression analysis showed that self-confidence (ß =0.522) and concentration recovery (ß = 0.377) are significant determinants of performance which explain totally 26.7 percent of the elite male trampolines' competitive performance. Findings of this study suggest that, in the high competitive level of trampoline, psychological factors (i.e., self-confidence and concentration recovery) have more predictive role which must be considered in preparation programs of elite male trampolines.